Cognitive Conflict Strategy and Simulation Practicum to Overcome Student Misconception on Light Topics - Wartono Wartono; John Rafafy Batlolona; Apilya Putirulan (Intelektual Pustaka Media Utama, 2018)
One way to reduce misconceptions can be overcome by cognitive conflict learning strategies with the help of simulation practicum instead of actual practicum. This study aims to determine whether there are differences in students' misconceptions before and after learning with cognitive conflict strategies as an effort to reduce misconceptions on light material. Research sample of 31 students. Data on the degree of misconception before the study was 0, 36 and after doing research was 0.17. The t-paired test results for the mean percentage of students' misconceptions on light material before and after learning differed at a significance level of 0.05. While, the results of N-Gain calculations to student achievement increase in overcoming misconceptions on light material were 0.3, that means the average students’ achievement in dealing with misconceptions are in the medium category and cognitive conflict strategies combined with simulation practicum have a strong effect on reducing students' misconceptions on light material with a range of 2.91. Based on the results of the study it can be concluded that cognitive conflict strategies combined with simulation practicum can be used to reduce misconceptions that lead to increased student learning achievement. Further research is needed to explore students' misconceptions on other physics topics and can measure student misconceptions at each meeting so that students are more organized and developed in learning.